Counterpoints from the “heroic” to the “fantastic”: institutionalization of national music, “black” “popular” resistance practices and interculturality in Cartagena de Indias - Cabarcas Ortega, Marcelo José (2022)
This paper depicts popular music as both hybrid dynamics and space of symbolic and material resistance, that is, as an interplay between canonic and subalternized cultural forms. It departs from the idea of hybridity to analyze the adaptability and resistance of cultural movements and, in such way, reflect on the past and present of specific Colombian Caribbean’s societal settings. Three aspects are addressed here to this end: first, the institutionalization of high-end national music and its impact on shaping the vernacular; second, the relationship between the official culture and the “popular”, black, vernacular practices; and third, the interactions between the hegemonic and the subordinate as a means of reconfiguring daily life’s rhythms and styles. The standpoint of this text is essay-like and interdisciplinary, pertaining to cultural studies, and its aim is to contribute to the current debates on culture, marginalization and resistance in the Colombian Caribbean, in particular, and the Hispanic Caribbean, in general.